Kipimoojikewin: Articulating Anishinaabe Pedagogy Through Anishinaabemowin (Ojibwe Language) Revitalization - Chacaby, Maya
In Anishinaabemowin (Ojibwe language), Kipimoojikewin refers to our inheritance, or the things we carry with us. While Anishinaabemowin, Anishinaabe (Ojibwe) pedagogy and research practices are all part of our inheritance, so too is a legacy of colonial violence and historic trauma. This paper details one journey towards the language; the struggle through a colonial terrain rife with institutional and cognitive barriers, the journey to return to Anishinaabe ways of knowing, to articulating Anishinaabe pedagogy in a contemporary urban context and the work done to fulfill the vision of the Elders. There are no “best practices” only stories that exemplify an Anishinaabe axiological framework so that the causes and effects can be better understood, taken up and improved upon. Aapajitoon kema wanitoon. MAST